Model Strategi Pemberdayaan Pendidik dan Masyarakat dalam Penjaminan Mutu Pendidikan Berbasis Mitigasi Bencana di Sekolah Lahan Basah - Rovana, Septy; Suriansyah, Ahmad (Lembaga Teewan Journal Solutions, 2026)
Educational quality assurance concerns not only academic achievement but also school safety and disaster preparedness. In wetland areas such as South Kalimantan Province, hydrometeorological disasters, particularly flooding, pose significant challenges to the continuity of education services. Data from BAN-PDM (2025) indicate that 39.6% of schools/madrasahs remain in the low and moderate categories for disaster mitigation indicators. This study aims to analyze strategies for empowering educators and communities to strengthen disaster mitigation-based educational quality assurance. A qualitative approach with an intrinsic case study design was employed at MTs Pangeran Muhammad Noor, Banjarmasin. Data were collected through in-depth interviews, observation, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that low disaster preparedness is influenced by the absence of systematic evacuation procedures, limited educator capacity, minimal community participation, and the lack of integrated strategies for learning continuity and psychosocial recovery. The study proposes an integrative and cyclical system-based empowerment model encompassing educator empowerment, community participation, disaster procedures and simulations, and continuous evaluation across pre-disaster, disaster, and post-disaster phases. The findings highlight the importance of integrating disaster mitigation into educational quality assurance systems to support resilient and sustainable schools in wetland areas.